Prototype of water quality monitoring mobile application as early warning system based on internet of things - Pandawana, I Dewa Gede Agung; Partama, I GD Yudha; Dwipa, I Made Suryana; Sari, Putri Agung Permata; Kumara, Dewa Gede Agung Gana (SEAN Institute, 2024)
Implementing IoT technology in intelligent aquaculture, including water quality surveillance based on IoT data, represents a viable strategy for enhancing the calibre and output of aquaculture. Farmers are able to autonomously gather water quality data and relay it to the control system in a timely manner so that appropriate measures can be taken. This practice not only contributes to the enhancement of aquaculture quality but also mitigates production expenses and ecological footprint. Using the prototyping method, an IoT-based water quality monitoring application prototype was developed for this study. This procedure is ideally suited for satisfying user requirements and developing effective applications. The findings of the study indicate that the primary purpose of this application is to precisely monitor and report water quality conditions (temperature, pH, turbidity, and oxygen levels) in real time, without the need to physically visit the fish farming site. Additionally, the application incorporates an Early Warning System (EWS) that notifies users via Telegram Group and Android phone alarms when water quality deteriorates. Furthermore, the application integrates the most recent weather data at the fish aquaculture site with the Balinese lunar calendar (Sasih), providing supplementary insights into the present state of the surrounding environment and the impact of Sasih. Furthermore, this application incorporates a notification alarm message functionality that, when the water quality of the fish aquaculture location falls below a specified threshold, enables multiple members of the Telegram Group to receive alert messages. With the integration of these functionalities, the water quality monitoring application is anticipated to significantly contribute to the real-time management, surveillance, alleviation, and regulation of water quality.